Kajian tentang sikap, pengetahuan sedia ada, gaya pembelajaran dan pencapaian akademik pelajar lepasan politeknik dan matrikulasi - Megat Zakaria, Megat Aman Zahiri (2018)
The purpose of this study is to identify the level of attitude, existing knowledge as well as the polytechnic and matriculation of student learning styles. In addition, it also aims to identify differences in attitudes, existing knowledge and learning styles among postgraduate students in polytechnic and matriculation. The relationship of learning styles to students' academic achievement in polytechnic and matriculation is also examined. This study was conducted at the School of Education, University of Technology Malaysia. Respondents consisted of 136 Year 1, 2 and 4 students majoring in Mechanical, Building and Electrical and Electronics. Quantitative methods using the questionnaire form were used for this study. The frequency, percentage and mean obtained indicate the level of attitude, existing knowledge as well as the polytechnic and matriculation students' learning styles. Tests were conducted to identify differences in attitudes, existing knowledge and learning styles among postgraduate and matriculation students. The findings showed that there were no significant differences in attitude, existing knowledge and significant learning styles among postgraduate students in polytechnic and matriculation. The Pearson correlation test was used to examine the relationship of learning style factors to students' academic achievement in polytechnic and matriculation. The results show that there is no significant relationship between the learning style factors to the academic achievement of the polytechnic and matriculation students.